Need for Radiation Diagnosis in Pediatric Practice (Eurasian Medical Research Periodical, 2023)
One of the significant factors influencing the nature and outcome of treatment measures is a complete and timely diagnosis of various diseases in children. This is especially true in the early stages of the disease, when adequate therapy can significantly affect the nature of the development of the pathological process.